Estudo da intera????o in vitro de Sclerotinia sclerotiorum com diferentes hospedeiros - Maximiano, Mariana Rocha (2015)
Sclerotinia sclerotiorum, the causal agent of white mold, is a plant pathogenic fungus that has a characteristic feature, production of sclerotia, resistance structures that can be viable for up to 10 years in the soil, with ability to initiate a new cycle of infection under favorable conditions. The disease control methods are based on integrated management practices, including biological and chemical control. The proteomic study of this interaction may be a strategy for studying this pathosystem, however, the small amount of mycelium produced during the infectious process in vivo greatly limits the study of this pathosystem using this strategy. The main goals of this work were the development and validation of a culture medium that would partially mimic the host and allow the production of large amounts of micelium for in vitro studies of this pathosystem. For this purpose, a protocol was established for the production of culture media prepared with leaf extract of the hosts. These media were inoculated with sclerotia of the monosporic isolate SS 200 of S. sclerotiorum and the differential expression of effectors and candidate effectors of virulence of the fungus was evaluated by qPCR. The results showed that a large amount of micelia grew in the media and effector genes and candidate effector genes were induced in these media. These results indicate that the proposed culture media can be used to study the in vitro interaction between S. sclerotiorum and several plant hosts and that they can be useful especially in proteomic studies.